PENGARUH JENIS KAYU DAN KOMPOSISI PEREKAT UREA FORMALDEHIDATERHADAP KETEGUHAN REKAT KAYU LAPIS BEBERAPA JENIS KAYU HUTAN TANAMAN INDUSTRI - Suwandi Kliwon; M I lskandar; Paribroto Sutigno (Jurnal Penelitian Hasil Hutan, 1988)
A glue shear test  was conducted   using plywood panel,  made  from  three  wood  species  namely pine  (Pinus merkusii Yung  et de  Vr.),  Eucalyptus alba and Eucalyptus deglupta from  West Java.  The bolts were rotary peeled  into  veneer of  1.5 mm  thick.The  veneer  sheets  were glue  with  urea formaldehyde   resin in combination with  meranti  and kapur  veneers.  Each plywood  sample  thus consisted  of three layer veneer and meranti  merah (red meranti)  and kapur (Dryobalanops  oramatica Gaert) as face and  back  veneers.The  bonding  strength  (glue shear strength)   of  each plywood  type  were then  tested according  to the Indonesian  and Japaneess  standard. The  result  indicates  that  there  were  significant differences between wood  species  and  variation  of extender   composition    according   to  the  Indonesian standard and  only  percentage   of  extenders  indicated significant difference   using Japaneess standard.  Percentage  10%  extender   was the  best bonding  strength  of plywood  comprising  with the  others.